Haemarthrosis stimulates the synovial fibrinolytic system in haemophilic mice - Nieuwenhuizen, Laurens; Roosendaal, Goris; Coeleveld, Katja; Lubberts, Erik; Biesma, Douwe H.; Lafeber, Floris P. J. G.; Schutgens, Roger E. G. (Thrombosis and Haemostasis, 2013)
Recurrent joint bleeding is the most common manifestation of haemophilia resulting in haemophilic arthropathy (HA). The exact pathophysiology is unknown, but it is suggested that arthropathy is stimulated by liberation of fibrinolytic activators from the synovium during haemarthrosis. The aim of this study was to test the hypothesis that haemarthrosis activates the local synovial fibrinolytic system in a murine haemophilia model. The right knees of haemophilic and control mice were punctured to induce haemarthrosis. The left knees served as internal control joints. Synovial levels of urokinase-type plasminogen activator (uPA), plasminogen activator inhibitor 1 (PAI-1), plasmin, and alpha-2-antiplasmin (A2AP) were compared between the punctured and control knees. In haemophilic mice, an increase in synovial cells expressing urokinase-type plasminogen activator (uPA) in the right punctured knee versus the left unaffected knee was observed: (47% vs 43%) (p=0.03). Additionally, in haemophilic mice, haemar-throsis induced an increase in uPA (0.016 ng/ml vs 0.01 ng/ml) (p=0.03) and plasmin (0.53 μg/ml vs 0.46 μg/ml) (p=0.01) as promoters of fibrinolysis. Synovial levels of PAI-1 (0.32 ng/ml vs 0.17 ng/ ml) (p<0.01) was also increased, whereas synovial levels of A2AP were unchanged: (0.021 μg/ml vs 0.021 μg/ml) (p=0.15). Enhanced uPA production was confirmed in human stimulated synovial fibroblast cultures and elevated levels of plasmin were confirmed harmful to human cartilage tissue explants. In this study we demonstrate that haemarthrosis in haemophilic mice induces synovial uPA expression and results in an increase in synovial plasmin levels, making the joint more vulnerable to prolonged and subsequent bleedings, and adding directly to cartilage damage.
Keywords: Fibrinolysis; haemophilia; haemarthrosis; synovium; haemophilic arthropathy